PENGARUH KEBISINGAN TERHADAP STRES KERJA PADA TENAGA KERJA DI INDUSTRI PENGGILINGAN PADI - Safitri, Dian (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2021)
Rice milling is one of the activities that produce high noise intensity, which can impact the health of workers. This study aims to determine the effect of noise on stress on workers at the Anugrah Mulya Rice Mill in Wates Village, Gadingrejo District, Pringsewu Regency, Lampung Province. The study used a cross-sectional design, carried out in February - May 2019. The sample is 35 workers, which is the whole of the population. Observations were made on noise sources and measured the noise level using a sound level meter. Measurements were made at 4 inside and 4 outside the room. Furthermore, interviews with workers used instruments to measure the work stress scale based on indicators or symptoms of stress, including physical symptoms, behavioral symptoms, and symptoms at work. Data were analyzed using Chi-Square statistical test. The results showed that the noise intensity in the rice milling room had exceeded the NAV of 87 dB(A) and caused work stress to 51.4% of workers. Age, gender, and noise also affect work stress. Measures to reduce noise exposure in the workplace and joint recreation for all workers can prevent work-related stress.